Party leaders’ selection and internal political party conflicts at the subnational level in Mexico - Guadarrama-Cruz, Carlos (Revista Elecciones, 2025)
This article analyzes the origin of intraparty conflicts in the state party presidencies selection processes within the PAN, PRI, PRD, and Morena in Mexico during the period 2010-2022. The study analyzes 438 selection processes using mixed-effects logistic regression tests to assess the hypothesis that electoral incongruence elevates the risk of conflict, a relationship that is moderated by high levels of local partisan institutionalization. The results show that when parties have solid organizational structures at the state level, conflicts tend to decrease, even if there is incongruence between the national and local electoral results. The study offers a theoretical and empirical contribution to the analysis of intraparty politics at subnational levels. In this way, the work proposes new lines of research on the topic of politics and conflicts within political parties.